Manajemen Operasi Masjid : Eksplanatori Pada Program Khutbah Jumat Di Masjid Kemayoran Surabaya - Adityo Nugroho; Muhammad Izzudin Al-Faruqi; Herma Musyanto; Agus Salim (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2019)
ABSTRACTThe Al-Munawwir Dictionary provides a definition of a mosque as a place of worship for Muslims, seen in terms of the mosque's etymology derived from the word sajada-sujud-masjad / mosque, which means obedient, obedient, and submissive with respect. This study aims to provide an overview of the strategy and management of the Friday sermon production process at the Kemayoran Mosque in Surabaya as its object. The method used by researchers in this research is a case study with data collection procedures using in-depth interviews, observation, and documentation. So that researchers can explore the phenomenon of the object of research in detail and depth. The findings that occur in the field show results that are sharpened by descriptive descriptions of several categories of production. First, the process of determining the idea of the Friday sermon program at the Kemayoran Mosque. Second, for the selection mechanism for Friday sermon program at Kemayoran Mosque. Third, the Friday sermon design program at Kemayoran Mosque. Fourth, testing and evaluating the Friday sermon program at Kemayoran Mosque. Fifth, the final design of the Friday sermon program at the Kemayoran Mosque.ABSTRAKKamus Al-Munawwir memberikan definisi Masjid sebagai tempat beribadah umat Islam, dilihat dari segi etimologi masjid berasal dari kata sajada-sujud-masjad/masjid, yang berarti taat, patuh, dan tunduk dengan hormat. Penelitian ini ditujukan untuk memberikan gambaran mengenai strategi dan manajemen proses produksi khutbah Jum’at di Masjid Kemayoran Surabaya sebagai objeknya. Metode yang digunakan oleh peneliti dalam penelitian ini ialah studi kasus dengan prosedur pengumpulan data menggunakan wawancara secara mendalam, observasi, dan dokumentasi. Sehingga peneliti dapat menggali fenomena pada objek penelitian secara rinci dan mendalam. Temuan yang terjadi di lapangan menunjukkan hasil yang dipertajam dengan uraian deskriptif mengenai beberapa kategori produksi khubah. Pertama, proses penentuan gagasan program khutbah Jum’at di Masjid Kemayoran. Kedua, untuk mekanisme seleksi program khutbah Jum’at di Masjid Kemayoran. Ketiga, desain program khutbah Jum’at di Masjid Kemayoran. Keempat, pengujian dan evaluasi program khutbah Jum’at di Masjid Kemayoran. Kelima, desain akhir program khutbah Jum’at di Masjid Kemayoran.